3(x+1)=2(x+3)+x-3

Simple and best practice solution for 3(x+1)=2(x+3)+x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+1)=2(x+3)+x-3 equation:



3(x+1)=2(x+3)+x-3
We move all terms to the left:
3(x+1)-(2(x+3)+x-3)=0
We multiply parentheses
3x-(2(x+3)+x-3)+3=0
We calculate terms in parentheses: -(2(x+3)+x-3), so:
2(x+3)+x-3
We add all the numbers together, and all the variables
x+2(x+3)-3
We multiply parentheses
x+2x+6-3
We add all the numbers together, and all the variables
3x+3
Back to the equation:
-(3x+3)
We get rid of parentheses
3x-3x-3+3=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| (3x-1)(3x+1)=15 | | x+x+x+x+4=10*x | | -2x+4=-6x+12 | | 6^2p=6^2p-3 | | 9-5x=28 | | 4b^2-10=78 | | x^-2=5/70 | | 25=3x^2 | | 5x-3=2-7x | | 20/4x-12=8 | | 12x+(4x-3)=60-(4x+3) | | 2(12x-6)=36 | | 2(3+4x)=6-4x | | -3+4x=61 | | 2p^2-20p=50 | | 60/4= | | 29-x=2x-1  | | 10x+25=4x | | 32p^2+50=0 | | 2^x+9×2^x=40 | | 4x-30+6x-30+3x+x=360 | | 3x+3=37 | | X+7/3=1+3x-2/5 | | 2y+5y-7y=0 | | 3(2x-50)=735 | | 5x+3=3x–5 | | 5.5x-14.3=7.7 | | 3x-3=2x7x | | 3r-2=5r+7 | | 1.5t^2-36t=0 | | (X)=2x-3x+7 | | 3.14159(d/2)^(2)=0 |

Equations solver categories